Low-conductivity polyolefin material and preparation method thereof

By mixing and radiating crosslinking the polyolefin matrix with the polyamide matrix, adding high molecular weight polyethylene particles and preparing crystalline fibers through electrospinning technology, and finally annealing in a vacuum furnace, the balance problem of polyolefin materials between low conductivity and mechanical properties is solved, and the effects of high mechanical strength, wear resistance and thermal stability are achieved.

CN119615413APending Publication Date: 2025-03-14ANGREEN DONGGUAN NEW MATERIALS TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411863396.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

While ensuring low conductivity, existing polyolefin materials are difficult to improve their mechanical properties and wear resistance, especially in high load and high friction environments.

Method used

The crosslinked mixed structure is formed by mixing the polyolefin matrix and the polyamide matrix and performing radiation crosslinking treatment using a high-energy radiation device. Then high molecular weight polyethylene particles are added and unidirectionally arranged crystalline fibers are prepared by electrospinning technology, and finally annealed in a vacuum furnace.

Benefits of technology

It achieves the material's mechanical strength, wear resistance and thermal stability while maintaining low conductivity, and is suitable for industrial applications in high-strength, high temperature and high friction environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615413A_ABST
    Figure CN119615413A_ABST
Patent Text Reader

Abstract

The invention discloses a low-conductivity polyolefin material and a preparation method thereof.The preparation method comprises the steps that a polyolefin matrix and a polyamide matrix are added into a reaction kettle, slowly heated to the first temperature and kept for 30-60 min, then slowly heated to the second temperature and kept for 60-90 min, and a preliminary mixed solution is obtained; performing radiation cross-linking treatment on the preliminary mixed solution based on high-energy radiation equipment to form a cross-linked mixed structure; heating and mixing the cross-linked mixed structure and high molecular weight polyethylene particles to form a cross-linked solution; adding a viscosity modifier into the cross-linking solution, putting the cross-linking solution added with the viscosity modifier into an injector of an electrospinning device, and obtaining unidirectionally arranged crystalline fibers through an electrospinning technology; and placing the crystallized fibers in a vacuum furnace for annealing treatment to obtain the polyolefin material with low conductivity. The problem of balance between mechanical strength and conductivity of the low-conductivity polyolefin material is effectively solved, and the low-conductivity polyolefin material is suitable for industrial application in high-strength, high-temperature and high-friction environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polyolefin materials, and in particular to a low-conductivity polyolefin material and a preparation method thereof. Background Art

[0002] With the increasing demand for high-performance materials in electronic technology, energy fields and industrial equipment, low-conductivity materials have received extensive attention and research in multiple application scenarios. Especially in electrical, electronic, and some high-precision mechanical equipment, the use of low-conductivity materials can effectively avoid electromagnetic interference, improve safety and extend the service life of equipment. As an important polymer material, polyolefin materials are widely used in insulation materials, electronic devices, cables and other fields due to their good chemical stability, low cost and good processing performance.

[0003] Existing polyolefin materials have good chemical resistance and low electrical conductivity, but their wear resistance, mechanical strength and thermal stability are relatively poor. Especially in applications that have strict requirements on material wear resistance and electrical conductivity, due to the low degree of polymerization of polyolefin materials and the greater flexibility of the molecular chain, they are prone to wear in high-load use environments, and have poor tensile strength and impact resistance, which makes the material less than ideal in many application scenarios that need to withstand mechanical stress and friction. Some processing methods in the prior art, such as improving the performance of composite materials through hot pressing and other methods, often find it difficult to improve the mechanical properties and wear resistance of the material while ensuring low electrical conductivity. These traditional methods are usually unable to simultaneously meet multiple requirements such as electrical conductivity, wear resistance, and mechanical strength, resulting in limited improvement in material performance, especially in complex industrial applications, and it is still difficult to meet high performance requirements. Summary of the invention

[0004] The purpose of the present application is to provide a low-conductivity polyolefin material and a preparation method thereof, so as to solve the technical problem that the existing polyolefin materials cannot ensure low conductivity while improving the mechanical properties and wear resistance of the materials.

[0005] To achieve this goal, this application adopts the following technical solutions: A method for preparing a low-conductivity polyolefin material, comprising: Adding a polyolefin matrix and a polyamide matrix into a reaction kettle, slowly heating to a first temperature and maintaining it for 30 to 60 minutes, and then slowly heating to a second temperature and maintaining it for 60 to 90 minutes to obtain a preliminary mixed solution, wherein the first temperature is the melting point temperature of the polyolefin, and the second temperature is the melting point temperature of the polyamide; Performing radiation cross-linking treatment on the preliminary mixed solution based on high-energy radiation equipment to form a cross-linked mixed structure; heating and mixing the cross-linked mixed structure with high molecular weight polyethylene particles to form a cross-linked solution; Adding a viscosity regulator to the cross-linking solution, placing the cross-linking solution with the viscosity regulator into a syringe of an electrospinning device, and obtaining unidirectionally arranged crystalline fibers by electrospinning technology; The crystalline fiber is placed in a vacuum furnace for annealing to obtain a polyolefin material with low electrical conductivity.

[0006] Further, the step of adding the polyolefin matrix and the polyamide matrix into a reaction kettle, slowly heating to a first temperature and maintaining it for 30 to 60 minutes, and then slowly heating to a second temperature and maintaining it for 60 to 90 minutes to obtain a preliminary mixed solution comprises: Adding a polyolefin matrix and a polyamide matrix into a reaction kettle, wherein the polyolefin matrix: polyamide matrix is ​​calculated by mass ratio of 1:0.25-0.35; The reactor is stirred, and the reactor is heated to the melting point of the polyolefin matrix at a heating rate of 2-5° C. / min, and maintained for 30-60 minutes, so that the polyolefin matrix and the polyamide matrix are fully melted and preliminary physical crosslinking occurs; The stirring process is accelerated to 5-10 rpm, the reaction kettle is heated to the melting point of the polyamide matrix at a heating rate of 1-3° C. / min, and the stirring is continued for 60-90 minutes to form the preliminary mixed solution.

[0007] Furthermore, after the step of adding the polyolefin matrix and the polyamide matrix into a reaction kettle, slowly heating to a first temperature and maintaining it for 30 to 60 minutes, and then slowly heating to a second temperature and maintaining it for 60 to 90 minutes to obtain a preliminary mixed solution, the method further comprises: The reactor is connected to a vacuum pump system, and the internal pressure of the reactor is maintained at a vacuum degree of 0.01-0.09 MPa through the vacuum pump system; The preliminary mixed solution in the reactor is stirred at a low speed for 10 to 20 minutes, and then the internal pressure of the reactor is made to be in a vacuum degree of 0.09 to 0.1 MPa by the vacuum pump system; The preliminary mixed solution is degassed under a vacuum degree of 0.09-0.1 MPa to remove bubbles in the solution.

[0008] Furthermore, the step of performing radiation cross-linking treatment on the preliminary mixed solution based on high-energy radiation equipment to form a cross-linked mixed structure includes: The obtained preliminary mixed solution is placed in the radiation area of ​​a high-energy radiation device for radiation cross-linking treatment, and the radiation dose of the high-energy radiation device is controlled to be 10-50 kGy; In the radiation area, obtaining temperature information of the preliminary mixed solution based on a temperature detector, and adjusting the radiation dose according to the temperature information; The preliminary mixed solution after the radiation cross-linking treatment is cooled to obtain a cross-linked mixed structure.

[0009] Furthermore, the step of obtaining the temperature information of the preliminary mixed solution based on a temperature detector and adjusting the radiation dose according to the temperature information includes: Setting a target temperature value based on a temperature difference between the melting points of the polyolefin matrix and the polyamide matrix; Acquire temperature data of multiple points in the radiation area based on the temperature detector, and perform denoising on the temperature data of the multiple points; Setting a weight ratio for each temperature data according to the distance between each temperature data and the high-energy radiation device, and performing weighted averaging on a plurality of the weight ratios to obtain a weighted temperature value; A difference between the weighted temperature and the target temperature value is calculated, and the radiation dose is adjusted based on the difference.

[0010] Furthermore, the step of heating and mixing the cross-linked mixed structure with high molecular weight polyethylene particles to form a cross-linked solution comprises: The cross-linked mixed structure is heated and mixed with high molecular weight polyethylene particles based on a screw extruder, wherein the heating temperature of the screw extruder is set to 180-220° C.; A cooling device is arranged at the outlet of the screw extruder to quickly cool the cross-linking solution.

[0011] Furthermore, the step of placing the cross-linking solution to which the viscosity modifier is added into a syringe of an electrospinning device and obtaining unidirectionally arranged crystalline fibers by electrospinning technology comprises: Setting the voltage of the electrospinning device to within 10 kV to 30 kV, and setting the distance between the syringe and the collecting plate to within 10 to 20 cm, wherein the collecting plate is used to collect the prepared crystalline fibers; Controlling the collecting plate to rotate at a speed of 100-200 rpm, so that the fibers passing through the electrospinning device are gradually arranged in a unidirectional manner on the collecting plate along the rotation direction, thereby obtaining a unidirectionally arranged polymer; The unidirectional fiber is subjected to high-frequency ultrasonic treatment to increase the movement speed of the molecular chains in the polymer to obtain unidirectionally arranged crystalline fibers.

[0012] Furthermore, the step of placing the crystalline fiber in a vacuum furnace for annealing to obtain a polyolefin material with low electrical conductivity comprises: The crystalline fiber is placed in a vacuum furnace, heated to 100-150° C. at a rate of 1-5° C. / min, and maintained for 1-3 hours to eliminate stress inside the fiber and optimize its crystalline structure; After annealing, the material is slowly cooled to room temperature to obtain a low conductivity polyolefin material.

[0013] Furthermore, the viscosity regulator is at least one of polyvinyl alcohol, phthalate, and epoxy resin.

[0014] The present application also discloses a low conductivity polyolefin material, which is prepared by the preparation method of the low conductivity polyolefin material described in any of the above items. The low conductivity polyolefin material comprises: a polyolefin matrix, a polyamide matrix and a high molecular weight polyethylene powder. Calculated by mass percentage, the polyamide matrix accounts for 18% to 20%, the high molecular weight polyethylene powder accounts for 10% to 15%, and the balance is the polyolefin matrix.

[0015] Compared with the prior art, this application has the following beneficial effects: The preparation method of the low-conductivity polyolefin material of the present application ensures compatibility by mixing polyolefin and polyamide matrix and enhancing the strength and temperature resistance of the material through radiation cross-linking. The addition of polyamide can reduce the conductivity and maintain it continuously. The addition of high molecular weight polyethylene particles improves the crystallinity, melt fluidity and mechanical properties of the material. The electrospinning technology makes the material have a unidirectionally arranged crystalline fiber structure, which enhances its wear resistance and tensile strength. The molecular structure of the material is improved by annealing treatment, further improving its stability and durability. The present application effectively solves the balance problem between mechanical strength and conductivity of low-conductivity polyolefin materials, and is suitable for industrial applications in high-strength, high-temperature and high-friction environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0017] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which this application can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by this application, should still fall within the scope of the technical contents disclosed in this application.

[0018] Figure 1 It is a schematic diagram of the overall steps of the preparation method of low conductivity polyolefin material; Figure 2 A schematic diagram of the steps of an embodiment of a method for preparing a low-conductivity polyolefin material; Figure 3 The figure is a schematic diagram of the steps of another embodiment of a method for preparing a low-conductivity polyolefin material. DETAILED DESCRIPTION

[0019] In order to make the purpose, features, and advantages of the invention of this application more obvious and easy to understand, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the embodiments described below are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0020] In the description of the present application, it should be understood that the terms "upper", "lower", "top", "bottom", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. It should be noted that when a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be a centrally arranged component at the same time.

[0021] The technical solution of the present application is further explained below with reference to the accompanying drawings and through specific implementation methods.

[0022] refer to Figures 1 to 3 The present application provides a method for preparing a low-conductivity polyolefin material, comprising: S1: adding a polyolefin matrix and a polyamide matrix into a reaction kettle, slowly heating to a first temperature and maintaining it for 30 to 60 minutes, and then slowly heating to a second temperature and maintaining it for 60 to 90 minutes to obtain a preliminary mixed solution, wherein the first temperature is the melting point temperature of the polyolefin, and the second temperature is the melting point temperature of the polyamide; In step S1, the polyolefin matrix and the polyamide matrix are accurately weighed according to the set mass ratio, which can be set to 3:1, and added to the reactor. After the matrix material is added, the stirring system of the reactor is turned on to rotate it at an appropriate rate to ensure the uniform distribution of the two matrix materials and avoid local overheating or overcooling of the material. Then, the mixture in the reactor is slowly heated, and the heating rate is set at a low level, and the temperature is gradually increased to the melting point temperature (first temperature) of the polyolefin. Depending on the type of polyolefin and the specific formula, the first temperature is set between 160°C and 180°C. In this process, the heating rate is controlled to avoid excessive temperature gradients caused by too fast heating to ensure uniform melting of the material. The heating process should be continuous and stable. Slow and uniform heating can ensure that the polyolefin matrix is ​​completely melted and begins to interact initially with the polyamide matrix. When the temperature in the reactor stabilizes at the first temperature, the temperature is maintained for 30 to 60 minutes. The purpose of this stage is to allow the polyolefin matrix to fully melt and have an initial physical interaction with the surface of the polyamide matrix. Through this process, the molecular chains of the polyolefin matrix will be effectively untied, making it more fluid, and the polyamide matrix will also begin to soften to a certain extent. The time to maintain this temperature section is critical. Too short a time may result in the polyolefin matrix not being completely melted, which will affect the subsequent mixing quality; too long a time may lead to overheating, causing the matrix to degrade and affecting the material properties. When the polyolefin matrix is ​​melted and stable, it is slowly heated to the melting point temperature of the polyamide (the second temperature). The heating rate at this time should be more gentle to avoid the impact of drastic temperature changes on the material structure. The second temperature is usually between 220°C and 260°C, depending on the type of polyamide selected and its melting point. The melting point of polyamide is higher than that of polyolefin, so at this stage, the polyamide matrix will further melt and interact deeply with the polyolefin matrix. At this time, the second temperature is maintained for 60 to 90 minutes, which is to promote the full melting of the polyamide matrix so that it can form a stable mixture with the polyolefin matrix. In this process, the molecular chains of the polyamide will be rearranged to form a structure that can be fused with the polyolefin matrix. By maintaining the second temperature for an appropriate time, the polyamide and polyolefin matrix will reach a higher degree of compatibility and form a stable preliminary mixed solution. The stirring speed of the reactor can be adjusted in time during the heating process to avoid the stratification of the polyolefin and polyamide matrix. At the same time, the temperature change of the reactor should be monitored at all times to ensure that the set temperature range is not exceeded. A temperature sensor or an infrared thermometer can be used to monitor the temperature change in the reactor in real time to ensure accurate control of the heating process. It is worth noting that in the present embodiment, the polyamide matrix is ​​added to improve the insulation of the material, so it can help maintain or reduce the electrical conductivity. The polyamide has a certain hindering effect on the conduction of electric current, thereby reducing the electrical conductivity of the overall material.

[0023] S2: performing radiation cross-linking treatment on the preliminary mixed solution based on a high-energy radiation device to form a cross-linked mixed structure; In step S2, the high-energy radiation equipment can be selected such as an electron beam or a gamma ray source to ensure the stability and uniformity of the radiation source. The preliminary mixed solution is placed in the radiation area of ​​the radiation equipment. The radiation dose is set according to the characteristics of the material and the required degree of crosslinking. The range of the radiation dose can be selected between 10 and 100 kGy so that the material can achieve the expected crosslinking effect without causing excessive degradation. During the radiation process, the mixed solution is uniformly exposed to the radiation field to avoid local over-irradiation or under-irradiation. After the radiation crosslinking treatment is completed, the material is cooled under a controlled environment to prevent internal stress and cracks caused by rapid cooling. Through this process, the molecular chains of the polyolefin and polyamide matrix will form a three-dimensional network structure through a crosslinking reaction, thereby giving the material excellent mechanical properties and thermal stability. After the radiation crosslinking is completed, the material is post-processed, such as cleaning and drying, to remove possible residues and impurities to ensure the purity and quality of the material.

[0024] S3: heating and mixing the cross-linked mixed structure with high molecular weight polyethylene particles to form a cross-linked solution; In step S3, adding high molecular weight polyethylene particles is to enhance wear resistance. Specifically, high molecular weight polyethylene particles are mixed with a cross-linked mixed structure in a certain ratio so that the high molecular weight polyethylene particles can be evenly dispersed in the cross-linked mixed structure. The mixing process needs to be carried out under heating conditions to reduce the viscosity of the high molecular weight polyethylene particles so that they are more easily fused with the cross-linked mixed structure. The heating temperature is controlled above the melting point of the high molecular weight polyethylene particles, for example, the heating temperature range can be set between 180°C and 220°C. During the mixing process, continuous stirring is performed to ensure uniform mixing and avoid particle aggregation. After mixing, the mixture is slowly cooled to form a uniform cross-linked solution.

[0025] S4: adding a viscosity regulator to the cross-linking solution, placing the cross-linking solution with the viscosity regulator into a syringe of an electrospinning device, and obtaining unidirectionally arranged crystalline fibers by electrospinning technology; In step S4, the viscosity regulator is added to make the viscosity in the cross-linking solution suitable for electrospinning. Specifically, a suitable viscosity regulator, such as polyethylene glycol or polypropylene glycol, is selected, and is measured and added to the cross-linking solution according to the initial viscosity of the cross-linking solution and the requirements of the electrospinning equipment, and is fully stirred and mixed to ensure that the regulator is evenly dispersed in the cross-linking solution. The treated cross-linking solution is placed in a syringe of an electrospinning device and spun by electrospinning technology. During the electrospinning process, the diameter and arrangement of the fiber are controlled by adjusting parameters such as voltage, the distance between the spinneret and the collecting plate, and the flow rate of the solution. The unidirectionally arranged crystalline fiber obtained by electrospinning has good mechanical properties and electrical insulation properties, and is suitable for the preparation of a variety of high-performance materials. Finally, the obtained fiber is collected and post-processed, such as heat treatment and stretching, to further improve the performance of the fiber. Through these steps, a polyolefin material with low electrical conductivity is finally prepared, which performs well in electrical insulation, heat resistance and mechanical strength, and is suitable for a variety of industrial applications.

[0026] S5: placing the crystalline fiber in a vacuum furnace for annealing to obtain a polyolefin material with low electrical conductivity.

[0027] In step S5, annealing treatment helps to eliminate stress inside the fiber and improve the crystallinity and electrical insulation properties of the material. During the annealing process, the crystalline fiber is placed in a vacuum furnace, and the pressure in the furnace is maintained at a low level, so that the fiber will not be oxidized during the heating process. Set the annealing temperature and time, and the annealing temperature can be set to be lower than the melting point of the material to avoid melting of the material. The annealing time is generally between 1 and 4 hours, and the specific time depends on the type of material and the required performance. During the annealing process, the molecular chains of the material will be rearranged to form a more stable crystal structure, thereby improving the overall performance of the material. After the annealing is completed, the material is slowly cooled to room temperature to prevent internal stress and cracks caused by rapid cooling. The resulting polyolefin material has excellent electrical insulation properties and low electrical conductivity, which can meet application scenarios with strict requirements in terms of electrical insulation, heat resistance and mechanical strength.

[0028] In steps S1-S5, the present application adds polyamide to reduce the conductivity of the material. Due to the poor compatibility of polyolefin and polyamide, phase separation often occurs during physical mixing, resulting in uneven performance of the composite material. By heating and mixing the polyolefin matrix and the polyamide matrix under specific temperature conditions (heated to the melting point of the polyolefin and the polyamide, respectively), the present application can ensure the full melting and uniform mixing of the two matrices under good temperature control conditions, thereby significantly improving the compatibility of the two so that the final preliminary mixed solution has good uniformity. Further, in existing low-conductivity materials, the reduction in conductivity is often accompanied by the sacrifice of mechanical properties, especially in applications where high mechanical properties and wear resistance are required, the brittleness of the material is particularly prominent. The present application successfully forms a cross-linked structure between the polyolefin and polyamide matrices by using high-energy radiation equipment to perform radiation cross-linking treatment on the preliminary mixed solution. Radiation cross-linking effectively improves the mechanical properties of the material, enhances its wear resistance, and also improves the thermal stability of the material. Furthermore, the present application uses electrospinning technology to add a viscosity regulator to a cross-linking solution, and obtains unidirectionally arranged crystalline fibers through an electrospinning device. The electrospinning technology can control the diameter and arrangement direction of the fibers to obtain a fiber material with excellent mechanical properties. In addition, the crystalline fibers obtained by the electrospinning process have a higher degree of crystallinity, which further improves the tensile strength and tensile properties of the material. The unidirectional arrangement of the fibers helps the material to maintain good mechanical properties when subjected to external forces, especially when subjected to stretching and friction, which can effectively reduce wear and deformation. Further, by placing the crystalline fibers obtained by electrospinning in a vacuum furnace for annealing, the present application further improves the microstructure of the material, so that the molecular chains in the fibers are arranged in order during the heat treatment process, thereby improving the stability and comprehensive performance of the material. The mechanical properties of the annealed polyolefin material are significantly enhanced while maintaining low conductivity. Annealing helps to reduce the residual stress inside the fiber, thereby improving its wear resistance and anti-aging ability.

[0029] In summary, the low-conductivity polyolefin material of the present application not only effectively reduces the conductivity through the combination of the above-mentioned multi-step processes, but also achieves significant improvements in improving the mechanical strength, wear resistance, thermal stability, etc. of the material. Although the existing low-conductivity polyolefin material has low conductivity, its wear resistance and mechanical strength often cannot meet the needs of high-performance applications. The material of the present application overcomes this limitation and can simultaneously meet the multiple performance requirements of low conductivity and good wear resistance, mechanical strength, etc., making its application prospects in harsh environments such as high strength, high friction, and high temperature broader.

[0030] In one embodiment, the step of adding the polyolefin matrix and the polyamide matrix into a reaction kettle, slowly heating to a first temperature and maintaining for 30 to 60 minutes, and then slowly heating to a second temperature and maintaining for 60 to 90 minutes to obtain a preliminary mixed solution comprises: Adding a polyolefin matrix and a polyamide matrix into a reaction kettle, wherein the polyolefin matrix: polyamide matrix is ​​calculated by mass ratio of 1:0.25-0.35; The reactor is stirred, and the reactor is heated to the melting point of the polyolefin matrix at a heating rate of 2-5° C. / min, and maintained for 30-60 minutes, so that the polyolefin matrix and the polyamide matrix are fully melted and preliminary physical crosslinking occurs; The stirring process is accelerated to 5-10 rpm, the reaction kettle is heated to the melting point of the polyamide matrix at a heating rate of 1-3° C. / min, and the stirring is continued for 60-90 minutes to form the preliminary mixed solution.

[0031] In this embodiment, a reactor capable of temperature control and stirring is provided, so that the interior of the reactor is clean and free of moisture to avoid interference of moisture on subsequent reactions. The polyolefin matrix and the polyamide matrix are added to the reactor in a mass ratio of 1:0.25~0.35, that is, 25g to 35g of polyamide matrix are added to every 100g of polyolefin matrix. The polyolefin matrix is ​​polyethylene (PE) or polypropylene (PP), and the polyamide matrix is ​​nylon (PA), which has high strength and heat resistance, can improve the thermal stability of the mixed material and enhance the physical cross-linking effect. In the reactor, the two matrixes are added after weighing, and the heating and stirring system of the reactor is started. Specifically, the heating rate is controlled to be 2~5℃ / min, and the temperature is gradually increased to the melting point of the polyolefin matrix. The melting point of polyolefin (such as polyethylene) is between 130~170℃, and the heating process is kept at a relatively slow rate, the purpose is to avoid premature melting of the matrix surface or excessive local temperature caused by too fast a temperature increase, thereby causing uneven heating and material decomposition. When the temperature in the reactor reaches the melting point of the polyolefin matrix, maintain the temperature for 30 to 60 minutes to fully melt the polyolefin matrix and the polyamide matrix. At this time, the molecular chains of the polyolefin matrix begin to flow with each other, and the polyamide matrix also undergoes physical crosslinking with the polyolefin matrix in this process. When the polyolefin matrix and the polyamide matrix are fully melted and begin to be initially crosslinked, accelerate the stirring speed and increase the stirring speed in the reactor to 5 to 10 rpm so that the two matrices can continue to mix and crosslink under uniform conditions. After accelerating the stirring, continue to increase the temperature of the reactor at a slower heating rate (1 to 3 ° C / min) to the melting point of the polyamide matrix, between 200 and 250 ° C. The heating rate of this process is slower than that of the previous stage, in order to prevent the polyamide matrix from melting too early and causing too fast a reaction, resulting in material inhomogeneity. After reaching the melting point temperature of the polyamide matrix, continue to heat and maintain the temperature for 60 to 90 minutes while continuing to stir. At this time, the molecular chains of the polyamide matrix begin to undergo further cross-linking reactions with the polyolefin matrix to form a more stable physical cross-linking structure. After the above-mentioned heating, stirring and cross-linking treatment, the mixture in the reactor will become a preliminary mixed solution with a certain fluidity and viscosity. The polyolefin and polyamide matrix in the mixture have formed a relatively stable structure through physical cross-linking. At this time, the material in the reactor has good uniformity, and the cross-linking effect begins to appear, but it has not yet reached the final cross-linking state.

[0032] In one embodiment, after adding the polyolefin matrix and the polyamide matrix into a reaction kettle, slowly heating to a first temperature and maintaining for 30 to 60 minutes, and then slowly heating to a second temperature and maintaining for 60 to 90 minutes to obtain a preliminary mixed solution, the step further includes: The reactor is connected to a vacuum pump system, and the internal pressure of the reactor is maintained at a vacuum degree of 0.01-0.09 MPa through the vacuum pump system; The preliminary mixed solution in the reactor is stirred at a low speed for 10 to 20 minutes, and then the internal pressure of the reactor is made to be in a vacuum degree of 0.09 to 0.1 MPa by the vacuum pump system; The preliminary mixed solution is degassed under a vacuum degree of 0.09-0.1 MPa to remove bubbles in the solution.

[0033] In this embodiment, after obtaining the preliminary mixed solution, the quality of the mixture is further improved by vacuum treatment to remove the bubbles that may exist therein. First, the reactor is connected to the vacuum pump system, and the reactor and the vacuum pump system are connected by a high temperature resistant and well-sealed pipeline, so that no gas leakage occurs during operation. At this time, the mixture in the reactor is in a preliminary stable state, but may still contain certain bubbles or dissolved gases, which will affect the quality of the final product in the subsequent material processing process, so it is necessary to remove them. Through the vacuum pump system, the gas in the reactor can be extracted under control to achieve the purpose of degassing. After connecting the vacuum pump system, it is necessary to adjust the vacuum degree in the reactor to within the range of 0.01~0.09MPa. This vacuum degree range is relatively low, which can effectively reduce the dissolved gas in the solution and promote the bubbles in the preliminary mixed solution to gradually rise to the surface. During the vacuum treatment process, the bubbles will become more affected by the vacuum and begin to escape to the surface of the solution. At this time, due to the low pressure, the volume of the bubbles expands, making it easier to be removed. Next, the reactor will be stirred at a low speed, and the stirring speed is controlled in the low speed range (10~20 rpm) to avoid excessive stirring speed causing the liquid to churn violently or generate new bubbles. Low-speed stirring helps to maintain the uniformity of the solution and ensure that the bubbles are evenly distributed and gradually rise to the surface of the liquid. This process generally needs to be maintained for 10~20 minutes, which is enough time for the bubbles in the solution to be completely discharged and to avoid the generation of new bubbles during stirring. After completing the low-speed stirring and ensuring that the bubbles are basically eliminated, the pressure inside the reactor is adjusted to 0.09~0.1MPa. The vacuum degree at this time is slightly higher than the initial 0.01~0.09MPa range, which helps to further enhance the degassing effect. At this time, since the vacuum degree is still maintained in a low range, the residual bubbles in the mixed solution will continue to rise and escape. The entire degassing process usually takes a certain period of time to ensure that the bubbles in the solution are almost completely removed. At this stage, the vacuum pump system can work by continuously pumping air or by adjusting the switching cycle of the vacuum pump. In this pressure range, the overflow rate of bubbles is fast, which can effectively reduce the impact of bubbles on the final mixed solution. The time and intensity of degassing need to be adjusted according to the properties of the solution to ensure that the surface of the treated solution is smooth and there are no obvious bubbles. During the vacuum degassing treatment, the temperature of the reactor is not lower than the melting point of the polyolefin matrix to avoid condensation or crystallization of the solution. In addition, the appropriate stirring speed can promote the rise of bubbles and accelerate their escape. The entire degassing process can work together with the temperature control and stirring of the reactor to ensure that all bubbles can be successfully removed and the final quality of the mixture reaches the ideal state.

[0034] In one embodiment, the step of performing radiation cross-linking treatment on the preliminary mixed solution using a high-energy radiation device to form a cross-linked mixed structure includes: S21: placing the obtained preliminary mixed solution in a radiation area of ​​a high-energy radiation device for radiation cross-linking treatment, and controlling the radiation dose of the high-energy radiation device to be 10-50 kGy; S22: in the radiation area, obtaining temperature information of the preliminary mixed solution based on a temperature detector, and adjusting the radiation dose according to the temperature information; S23: Cooling the preliminary mixed solution after the radiation cross-linking treatment to obtain a cross-linked mixed structure.

[0035] In this embodiment, the preliminary mixed solution is placed in the radiation area of ​​the high-energy radiation device. The high-energy radiation device can use an electron accelerator or a gamma ray source to generate high-energy electron beams or gamma rays, and the polymer chains are subjected to radiation cross-linking treatment through these high-energy radiations. The radiation dose of the high-energy radiation device is controlled to be 10~50 kGy (kiloGray). In the radiation area, a temperature detector is installed to monitor the temperature of the solution in real time. The temperature detector can be a thermocouple, an infrared sensor or other high-precision temperature measurement device for tracking the temperature information of the mixed solution. Through temperature monitoring, timely adjustments can be made when the solution temperature deviates from the ideal range. When the temperature is too high, the temperature can be lowered by adjusting the power of the radiation device or changing the radiation intensity; when the temperature is too low, the cross-linking reaction can be promoted by increasing the radiation dose or appropriately increasing the radiation time. The adjustment of the radiation dose is dynamically carried out according to the real-time temperature information. When the temperature rises, the rate of the cross-linking reaction may accelerate, and the radiation dose may need to be appropriately reduced to avoid excessive cross-linking; on the contrary, when the temperature is low, appropriately increasing the radiation dose helps to enhance the cross-linking effect, so that the radiation dose and temperature maintain a dynamic balance to ensure the best effect of the cross-linking process. After the radiation cross-linking treatment is completed, the preliminary mixed solution will experience a certain temperature change. The high temperature during the radiation process may cause the molecular chains of the material to cross-link, but it will also cause heat accumulation on the surface or inside of the material. Therefore, cooling treatment is required to reduce the temperature of the solution to a safe range to prevent overreaction or thermal degradation. The cooling treatment is achieved by natural cooling or forced cooling systems (such as cooling water circulation, air flow cooling, etc.). The speed and temperature of the cooling process should be properly controlled to avoid uneven cross-linking structure or internal stress due to too fast or too slow cooling. In general, the cooling time can be adjusted according to the mass and volume of the mixture to ensure that the material temperature returns to the room temperature range. After the cooling treatment, a cross-linked mixed structure is obtained, and the cross-linked polymer chains form a more solid three-dimensional network structure in the chemical structure, which greatly enhances the heat resistance, chemical corrosion resistance, mechanical strength and stability of the material.

[0036] In one embodiment, the step of obtaining the temperature information of the preliminary mixed solution based on a temperature detector and adjusting the radiation dose according to the temperature information includes: S24: setting a target temperature value based on the temperature difference between the melting points of the polyolefin matrix and the polyamide matrix; S25: acquiring temperature data of multiple points in the radiation area based on the temperature detector, and performing denoising processing on the temperature data of the multiple points; S26: setting a weight ratio for each temperature data according to the distance between each temperature data and the high-energy radiation device, and performing weighted averaging on a plurality of the weight ratios to obtain a weighted temperature value; S27: Calculate the difference between the weighted temperature and the target temperature value, and adjust the radiation dose based on the difference.

[0037] In this embodiment, during the radiation cross-linking process, there is a certain difference in the melting point of the polyolefin matrix and the polyamide matrix. In order to achieve the best cross-linking effect during the radiation process, a target temperature value is set according to the difference in the melting points of the two matrixes. Specifically, the melting point of polyolefin is between 100°C and 150°C, and the melting point of the polyamide matrix is ​​between 210°C and 270°C. According to the difference in the melting points of the polyolefin and polyamide matrixes, a target temperature value is set, and the target temperature value should take into account the melting point ranges of the two matrixes, so that the radiation cross-linking can fully promote the cross-linking reaction without causing excessive melting of the material. Specifically, the target temperature value can be set by using a nonlinear weighting coefficient to set the temperature, so as to better optimize the radiation cross-linking process, and introduce a temperature weighting coefficient β, whose value depends on the thermal stability of the polyolefin and polyamide matrices and the cross-linking reaction activity of the material. In this case, the calculation formula of the target temperature value is: ,in, is the target temperature value, is the melting point of the polyolefin matrix, is the melting point of the polyamide matrix, and β is a coefficient adjusted according to the thermal stability of the material, the cross-linking reaction rate, and actual production experience, and the selection range is between 0.4 and 0.6. Since polyolefins (such as polyethylene and polypropylene) have a lower melting point and may degrade or change in performance at higher temperatures, polyamides (such as nylon) have a higher melting point and better thermal stability. Therefore, when selecting the β value, if the polyolefin matrix is ​​more sensitive to temperature changes (for example, it is easy to degrade), the β value should be lower so that the temperature will not be too high to avoid affecting the performance of the polyolefin; if the polyamide matrix is ​​more easily degraded or loses thermal stability at a lower temperature, the β value can be appropriately increased to keep the temperature close to the melting point of the polyamide and avoid insufficient cross-linking due to too low a temperature, that is, the β value is adjusted according to the solubility of the polyolefin matrix and the polyamide matrix.

[0038] Furthermore, a temperature detector is arranged in the radiation area, and the temperature data of multiple points in the radiation process are obtained through the detector. The temperature data reflects the real-time situation of the temperature distribution in the radiation area, which can help determine the heating situation of each area and whether there is overheating or low temperature. Due to the influence of factors such as environmental noise, equipment error and heat conduction, the temperature data may contain some errors and noise. In order to ensure the accuracy of the temperature data, it is necessary to denoise the multi-point temperature data, and the noise can be removed by taking the mean of the data within a certain range around each data point. Different temperature data are affected by the radiation intensity of high-energy radiation equipment to different degrees. The temperature change of the area far away from the radiation equipment may be small; while the radiation intensity of the area closer to the distance is large, and the temperature change is more significant. Therefore, it is necessary to set the weight ratio according to the distance between each temperature data and the radiation equipment. The specific operation is: for each temperature detection point, calculate its distance from the radiation equipment, and assign different weights to the temperature data of the point based on the distance. Generally, the temperature data of points closer to the radiation source are assigned higher weights, and the points farther away are assigned lower weights. The weight ratio can be calculated by the following formula: ,in, is the weight of the i-th temperature data, is the distance between the ith temperature detection point and the radiation source. All temperature data are weighted averaged according to their weights to obtain a weighted temperature value, which can comprehensively consider the temperature distribution of each point in the radiation area and reflect the difference in the impact of the distance from the radiation source on the temperature through the weight. The weighted average formula is as follows: , where T is the weighted temperature value, is the ith temperature data, is the weight of the i-th temperature data, and n is the number of temperature detection points. After obtaining the weighted temperature value, calculate the difference between the weighted temperature and the target temperature value. If the weighted temperature is lower than the target temperature value, it means that the temperature in the radiation area is low, which may lead to unsatisfactory cross-linking effect. At this time, the radiation dose should be increased; if the weighted temperature is higher than the target temperature value, it means that the temperature is too high, causing the material to overheat or degrade, and the radiation dose should be reduced. The radiation dose can be adjusted by controlling parameters such as the output power, radiation time or radiation frequency of the radiation source. The specific adjustment rules can be optimized by the PID control algorithm to ensure the best radiation cross-linking effect under different temperature conditions. The PID control algorithm is a prior art and will not be repeated here. Through the above method, the temperature in the radiation cross-linking process can be monitored and adjusted in real time to ensure that the polyolefin material achieves an ideal cross-linking effect during the radiation process, while avoiding degradation of the material due to overheating.

[0039] In one embodiment, the step of heating and mixing the cross-linked mixed structure with high molecular weight polyethylene particles to form a cross-linked solution comprises: The cross-linked mixed structure is heated and mixed with high molecular weight polyethylene particles based on a screw extruder, wherein the heating temperature of the screw extruder is set to 180-220° C.; A cooling device is arranged at the outlet of the screw extruder to quickly cool the cross-linking solution.

[0040] In this embodiment, before extrusion mixing, a cross-linked mixed structure and high molecular weight polyethylene particles are provided. The cross-linked mixed structure includes a cross-linking agent (such as peroxide, sulfur, etc.) and an auxiliary agent (such as an antioxidant, a stabilizer, etc.), which play a promoting or regulating role in the cross-linking process. High molecular weight polyethylene particles are the main substrate and have good mechanical properties and chemical stability. The mixing ratio of the two needs to be set according to the specific product requirements, for example, the mass ratio of the cross-linking agent is between 1-5%. The screw extruder is a device for achieving heating and mixing. The extruder is equipped with a twin screw or a single screw, and heating and mixing are performed under high temperature and high pressure conditions. The twin screw extruder can provide a more uniform mixing effect and is suitable for processing polymers with higher viscosity. The heating temperature of the screw extruder is set to 180°C~220°C. This temperature range is sufficient to activate the cross-linking agent and promote the cross-linking reaction, while avoiding excessive temperature causing polyethylene degradation. The specific heating temperature should be optimized according to the properties of the cross-linking agent used and the desired cross-linking effect. For example, peroxide cross-linking agents usually require higher temperatures to activate, while other types of cross-linking agents may require lower temperatures. The setting of the extruder temperature needs to be experimentally debugged to ensure that the cross-linking effect is balanced with the processing stability of the polyethylene particles. Inside the screw extruder, the cross-linked mixed structure and the high molecular weight polyethylene particles are fully mixed and heated at high temperature by the rotation of the extrusion screw. At this time, the polyethylene particles will gradually melt, the cross-linking agent will be evenly dispersed in the polyethylene matrix, and begin to cross-link with the polyethylene. At the outlet of the extruder, a cooling device is set to quickly reduce the temperature of the cross-linking solution to prevent excessive temperature from causing material degradation or overreaction. The cooling device usually adopts a water cooling or air cooling system. The water cooling system can reduce the material temperature to a safe range in a short time to avoid thermal stress causing instability in product morphology or performance. The cooling device needs to cover the entire area of ​​the extruder outlet and match the operating conditions of the extruder (such as screw speed, feed rate, etc.).

[0041] In one embodiment, the step of placing the cross-linking solution to which the viscosity modifier is added into a syringe of an electrospinning device and obtaining unidirectionally arranged crystalline fibers by electrospinning technology comprises: Setting the voltage of the electrospinning device to within 10 kV to 30 kV, and setting the distance between the syringe and the collecting plate to within 10 to 20 cm, wherein the collecting plate is used to collect the prepared crystalline fibers; Controlling the collecting plate to rotate at a speed of 100-200 rpm, so that the fibers passing through the electrospinning device are gradually arranged in a unidirectional manner on the collecting plate along the rotation direction, thereby obtaining a unidirectionally arranged polymer; The unidirectional fiber is subjected to high-frequency ultrasonic treatment to increase the movement speed of the molecular chains in the polymer to obtain unidirectionally arranged crystalline fibers.

[0042] In this embodiment, an appropriate amount of viscosity modifier is added to the cross-linking solution. The addition of the viscosity modifier can effectively increase the viscosity of the solution and improve the tensile properties and uniformity of the fibers during the electrospinning process. According to actual needs, during the electrospinning process, the voltage of the electrospinning device is adjusted to 10 kilovolts to 30 kilovolts. This voltage range can avoid excessive spraying or breaking of the solution while maintaining a certain electric field strength, ensuring the stability of the fiber morphology during the stretching process. The distance between the syringe and the collecting plate is set to 10 to 20 cm, which controls the flight trajectory of the fiber from the nozzle to the collecting plate. Too close a distance may result in incomplete fiber collection, and too far a distance may result in the fiber being affected by air resistance during flight, resulting in irregular shapes. By optimizing the distance between injection and collection, a more uniform fiber collection effect can be obtained. In order to obtain unidirectionally arranged crystalline fibers, a rotating collecting plate is provided in this embodiment, and the rotation speed of the collecting plate is controlled between 100 and 200 rpm to ensure that the fibers are gradually arranged in a unidirectional arrangement along the rotation direction during the collection process. The rotation of the collecting plate not only helps to improve the directionality of the fibers, but also avoids electrostatic aggregation and fiber accumulation. As the electrospinning process proceeds, the rotation of the collecting plate will continuously change the contact point of the fiber, so that the fiber gradually arranges in order along the direction of rotation. The material of the collecting plate can be selected from electrically insulating materials, such as aluminum or stainless steel, and ensure that its surface is smooth and flat, so as to better collect the electrospun fibers. The rotation speed of the collecting plate needs to be adjusted according to the viscosity of the fiber, the air humidity and the characteristics of the solution to ensure that the directional arrangement of the fiber achieves the best effect. After the fiber is collected, in order to further increase the movement speed of the molecular chain inside the polymer, thereby enhancing the crystallinity and physical properties of the fiber, a high-frequency ultrasonic treatment step is used in the embodiment. Ultrasonic waves can generate high-frequency vibration effects by inducing the propagation of sound waves in the solution. This vibration helps the movement of molecular chains and promotes the orderly arrangement and cross-linking reaction of molecular chains. The frequency of high-frequency ultrasonic treatment can be set between 20 kHz and 40kHz. The energy of ultrasonic waves can promote the movement and rotation between polymer molecules, reduce the movement barriers of internal molecular chains, thereby improving the crystallinity and making the physical properties of the fiber closer to the ideal state. After electrospinning and ultrasonic treatment, unidirectionally arranged crystalline fibers are obtained.

[0043] In one embodiment, the step of placing the crystalline fiber in a vacuum furnace for annealing to obtain a polyolefin material with low electrical conductivity comprises: The crystalline fiber is placed in a vacuum furnace, heated to 100-150° C. at a rate of 1-5° C. / min, and maintained for 1-3 hours to eliminate stress inside the fiber and optimize its crystalline structure; After annealing, the material is slowly cooled to room temperature to obtain a low conductivity polyolefin material.

[0044] In this embodiment, the crystalline fiber is placed in a vacuum furnace for annealing treatment in order to optimize the crystalline structure of the material and eliminate the internal stress that may be generated during the electrospinning process. By slowly heating to 100-150°C, it can be ensured that the crystalline fiber will not produce new defects due to excessive temperature changes during the heating process. The heating rate is controlled at 1-5°C / min to ensure that the temperature inside the material rises evenly and avoids the degradation of material performance caused by local overheating. After reaching the target temperature, maintaining a constant temperature treatment for 1-3 hours helps to rearrange the molecular chains inside the crystalline fiber and optimize the crystalline structure, thereby reducing the conductivity of the material. After annealing is completed, slowly cool to room temperature, because rapid cooling may cause new stress inside the material, affecting the conductivity and mechanical properties of the material. Through the above steps, the low-conductivity polyolefin material finally obtained has excellent electrical insulation properties and good mechanical strength, and is suitable for a variety of fields requiring low-conductivity materials. It is worth noting that in this application, the reactor, vacuum pump system, temperature detector, high-energy radiation equipment, screw extruder and cooling device are all prior art, that is, common equipment in the field of preparing polyolefin materials. The use methods and operating parameters of these devices, such as temperature, pressure, radiation dose, etc., can be appropriately adjusted according to the properties of the specific materials and the desired final product characteristics. For example, the size and shape of the reactor can be selected according to the production scale and the reaction characteristics of the material, and the vacuum pump system needs to determine its vacuuming ability according to the thermal stability of the processed material. The temperature detector is used to monitor the temperature changes during the reaction in real time to ensure that the reaction is carried out under safe and controllable conditions. High-energy radiation equipment is used to radiate cross-linking of materials to improve their physical and chemical properties. The screw extruder is used to plasticize and shape the treated material. Finally, the cooling device is used to quickly cool and solidify the extruded material to obtain the desired shape and size. Through the reasonable configuration and precise control of these devices, the performance of low-conductivity polyolefin materials can be accurately regulated to meet the needs of different application fields.

[0045] In one embodiment, the viscosity modifier is at least one of polyvinyl alcohol, phthalate, and epoxy resin.

[0046] In this embodiment, by adding a viscosity regulator, the viscosity of the electrospinning solution can be effectively controlled, thereby affecting the diameter and morphology of the fiber. Polyvinyl alcohol can increase the viscosity of the solution and make the fiber more uniform due to its good water solubility and adhesion. Phthalate compounds can be used as plasticizers to reduce the glass transition temperature of the material, so that the fiber has better processing properties at lower temperatures. The introduction of epoxy resin can increase the crosslinking density of the material and enhance the mechanical strength and heat resistance of the fiber. Different viscosity regulators can be selected according to different needs.

[0047] The present invention also discloses a low-conductivity polyolefin material, which is prepared by the preparation method of the low-conductivity polyolefin material as described in any one of the above items. The low-conductivity polyolefin material comprises: a polyolefin matrix, a polyamide matrix and a high-molecular-weight polyethylene powder. Calculated by mass percentage, the polyamide matrix accounts for 18% to 20%, the high-molecular-weight polyethylene powder accounts for 10% to 15%, and the balance is the polyolefin matrix.

[0048] As described above, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a low-conductivity polyolefin material, characterized in that: include: Adding a polyolefin matrix and a polyamide matrix into a reaction kettle, slowly heating to a first temperature and maintaining it for 30 to 60 minutes, and then slowly heating to a second temperature and maintaining it for 60 to 90 minutes to obtain a preliminary mixed solution, wherein the first temperature is the melting point temperature of the polyolefin, and the second temperature is the melting point temperature of the polyamide; Performing radiation cross-linking treatment on the preliminary mixed solution based on high-energy radiation equipment to form a cross-linked mixed structure; heating and mixing the cross-linked mixed structure with high molecular weight polyethylene particles to form a cross-linked solution; Adding a viscosity regulator to the cross-linking solution, placing the cross-linking solution with the viscosity regulator into a syringe of an electrospinning device, and obtaining unidirectionally arranged crystalline fibers by electrospinning technology; The crystalline fiber is placed in a vacuum furnace for annealing to obtain a polyolefin material with low electrical conductivity.

2. The method for preparing a low-conductivity polyolefin material according to claim 1, characterized in that: The step of adding the polyolefin matrix and the polyamide matrix into a reaction kettle, slowly heating to a first temperature and maintaining for 30 to 60 minutes, and then slowly heating to a second temperature and maintaining for 60 to 90 minutes to obtain a preliminary mixed solution comprises: Adding a polyolefin matrix and a polyamide matrix into a reaction kettle, wherein the polyolefin matrix: polyamide matrix is ​​calculated by mass ratio of 1:0.25-0.35; The reactor is stirred, and the reactor is heated to the melting point of the polyolefin matrix at a heating rate of 2-5° C. / min, and maintained for 30-60 minutes, so that the polyolefin matrix and the polyamide matrix are fully melted and preliminary physical crosslinking occurs; The stirring process is accelerated to 5-10 rpm, the reaction kettle is heated to the melting point of the polyamide matrix at a heating rate of 1-3° C. / min, and the stirring is continued for 60-90 minutes to form the preliminary mixed solution.

3. The method for preparing a low-conductivity polyolefin material according to claim 1, characterized in that: After the step of adding the polyolefin matrix and the polyamide matrix into a reaction kettle, slowly heating to a first temperature and maintaining for 30 to 60 minutes, and then slowly heating to a second temperature and maintaining for 60 to 90 minutes to obtain a preliminary mixed solution, the method further comprises: The reactor is connected to a vacuum pump system, and the internal pressure of the reactor is maintained at a vacuum degree of 0.01-0.09 MPa by the vacuum pump system; The preliminary mixed solution in the reactor is stirred at a low speed for 10 to 20 minutes, and then the internal pressure of the reactor is made to be in a vacuum degree of 0.09 to 0.1 MPa by the vacuum pump system; The preliminary mixed solution is degassed under a vacuum degree of 0.09-0.1 MPa to remove bubbles in the solution.

4. The method for preparing a low-conductivity polyolefin material according to claim 1, characterized in that: The step of performing radiation cross-linking treatment on the preliminary mixed solution based on a high-energy radiation device to form a cross-linked mixed structure includes: The obtained preliminary mixed solution is placed in the radiation area of ​​a high-energy radiation device for radiation cross-linking treatment, and the radiation dose of the high-energy radiation device is controlled to be 10-50 kGy; In the radiation area, obtaining temperature information of the preliminary mixed solution based on a temperature detector, and adjusting the radiation dose according to the temperature information; The preliminary mixed solution after the radiation cross-linking treatment is cooled to obtain a cross-linked mixed structure.

5. The method for preparing a low-conductivity polyolefin material according to claim 4, characterized in that: The step of obtaining the temperature information of the preliminary mixed solution based on a temperature detector and adjusting the radiation dose according to the temperature information comprises: Setting a target temperature value based on a temperature difference between the melting points of the polyolefin matrix and the polyamide matrix; Acquire temperature data of multiple points in the radiation area based on the temperature detector, and perform denoising on the temperature data of the multiple points; Setting a weight ratio for each temperature data according to the distance between each temperature data and the high-energy radiation device, and performing weighted averaging on a plurality of the weight ratios to obtain a weighted temperature value; A difference between the weighted temperature and the target temperature value is calculated, and the radiation dose is adjusted based on the difference.

6. The method for preparing a low-conductivity polyolefin material according to claim 1, characterized in that: The step of heating and mixing the cross-linked mixed structure with high molecular weight polyethylene particles to form a cross-linked solution comprises: The cross-linked mixed structure is heated and mixed with high molecular weight polyethylene particles based on a screw extruder, wherein the heating temperature of the screw extruder is set to 180-220° C.; A cooling device is arranged at the outlet of the screw extruder to quickly cool the cross-linking solution.

7. The method for preparing a low-conductivity polyolefin material according to claim 1, characterized in that: The step of placing the cross-linking solution containing the viscosity modifier into a syringe of an electrospinning device and obtaining unidirectionally arranged crystalline fibers by electrospinning technology comprises: Setting the voltage of the electrospinning device to within 10 kV to 30 kV, and setting the distance between the syringe and the collecting plate to within 10 to 20 cm, wherein the collecting plate is used to collect the prepared crystalline fibers; Controlling the collecting plate to rotate at a speed of 100-200 rpm, so that the fibers passing through the electrospinning device are gradually arranged in a unidirectional manner on the collecting plate along the rotation direction, thereby obtaining a unidirectionally arranged polymer; The unidirectional fiber is subjected to high-frequency ultrasonic treatment to increase the movement speed of the molecular chains in the polymer to obtain unidirectionally arranged crystalline fibers.

8. The method for preparing a low-conductivity polyolefin material according to claim 1, characterized in that: The step of placing the crystalline fiber in a vacuum furnace for annealing to obtain a polyolefin material with low electrical conductivity comprises: Placing the crystalline fiber in a vacuum furnace, heating it to 100-150° C. at a rate of 1-5° C. / min, and maintaining it for 1-3 hours to eliminate stress inside the fiber and optimize its crystalline structure; After annealing, the material is slowly cooled to room temperature to obtain a low conductivity polyolefin material.

9. The method for preparing a low-conductivity polyolefin material according to claim 8, characterized in that: The viscosity regulator is at least one of polyvinyl alcohol, phthalate, and epoxy resin.

10. A low conductivity polyolefin material, characterized in that: The low conductivity polyolefin material is prepared by the preparation method of any one of claims 1 to 9, wherein the low conductivity polyolefin material comprises: a polyolefin matrix, a polyamide matrix and a high molecular weight polyethylene powder, wherein, calculated by mass percentage, the polyamide matrix accounts for 18% to 20%, the high molecular weight polyethylene powder accounts for 10% to 15%, and the remainder is the polyolefin matrix.

Citation Information

Patent Citations

  • Self-reinforced polymer composite and preparation method thereof

    CN105524334A

  • Crosslinked polyolefin and preparation method thereof

    CN114854114A

  • Polymeric pipes and liners made from blends of polyolefins and polyamides

    CN1708548A

  • Polyamide-polyethylene materials with compatible polyethylene phase comprises polyamide and polyethylene, where the polyethylene comprises modified and unmodified polyethylene

    DE102005046571A1

  • Process for the preparation of polyolefin fibers

    IN201717044540A